1985
DOI: 10.1007/bf02935708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weights of fatty acid esters on cetane numbers as diesel fuels

Abstract: Cetane numbers for various esters of the saturated fatty acids from C8 to C18 have been determined according to ASTM D‐613. For the methyl esters the cetane numbers were found to increase in a non‐linear relationship with the chain length of the fatty acid. Cetane numbers of esters in which the fatty acid is kept constant while the alcohol esterified is altered also increased with the molecular weight of the ester. However, increases in the molecular weight of the fatty acid portion of the ester produce greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 5 publications
1
40
0
1
Order By: Relevance
“…Other factors may also play a role. For example, there is a positive correlation between CN and boiling point of a fatty compound (18). Another work, in which regression analyses were conducted, showed that boiling point was the most reliable property for predicting the CN of fatty compounds (19).…”
Section: Resultsmentioning
confidence: 95%
“…Other factors may also play a role. For example, there is a positive correlation between CN and boiling point of a fatty compound (18). Another work, in which regression analyses were conducted, showed that boiling point was the most reliable property for predicting the CN of fatty compounds (19).…”
Section: Resultsmentioning
confidence: 95%
“…The present work is intended to provide a reliable kinetic model for a methyl ester fuel that is much larger than the previous methyl butanoate. Instead of the 4 carbon atoms chain of methyl butanoate, the current work provides a kinetic mechanism for methyl decanoate (cetane number of about 47 [ 6,7]), with a chain of 10 carbon atoms with a methyl ester group attached ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…The infl uence of compound structure on CNs of fatty compounds was discussed (Harrington, 1986 ) and hypotheses confi rmed by practical cetane tests (Freedman et al , 1990 ;Ladommatos et al , 1996 ;Klopfenstein, 1985 ;. CNs of neat fatty compounds are given in Table 1.1 .…”
Section: Cetane Numbersmentioning
confidence: 99%
“…Transesterifi cation of fats or oils with medium -chain alcohols may increase CN, a parameter that can infl uence ignition quality and exhaust emissions (Klopfenstein, 1985 ). On the other hand, increased branching in saturated hydrocarbon chains also decreases CN.…”
Section: Transesterifi Cation With Medium or Branched Chain Alcoholsmentioning
confidence: 99%